Some Heavy Metal Contents Related With Different Physiographic Units and Land Use in Van Lake Basin - Siyami KARACA; Füsun GÜLSER (International Journal of Secondary Metabolite)
AbstractThe objective of this study was to determine the relations among some heavy metal contents related with different physiographic units and land use in Van Lake Basin. Surface soil samples (0-20 cm) were taken from forty different points having three different physiographic units (backslope, footslope and terrace) and three different land use (wheat, clover and pasture) in Van Lake Basin. The heavy metal contents (Al, Cd, Cr, Ni, Pb) changed due to land use and physiographic units. The means of Al, Cd, Cr, Ni and Pb varied between 103.567-68.174 ppm, 0.514- 0.448 ppm, 2.789-2.513 ppm, 2.139- 1.923 ppm and 0.247- 0.132 ppm respectively.Key words: land use, physiographic units, heavy metal contents.